Prevalence and pathogenicity of Cryptosporidium andersoni in one herd of beef cattle - Kvác, M; Vítovec, J (Journal of veterinary medicine. B, Infectious diseases and veterinary public health, 2003)
Over a 35-week period from January to July 2002, a breed of Hereford beef cattle (H) and their hybrids were monitored. Five hundred and ninety-nine individual fecal samples from calves and 96 samples from their mothers were examined. First excretion of Cryptosporidium andersoni oocysts in calves was found in the 9th week after the start of calving (a calf 63-day old). The prevalence of C. andersoni in calves ranged from 11.1 to 92.9% depending on age. The mean prevalence in their mothers was found to be 43.8%. The size of oocysts was 8.48 +/- 0.78 x 6.41 +/- 0.59 microm. Infection intensity in calves ranged from 32 000 to 4 375 000 oocysts per gram (OPG) and in mothers from 78 000 to 2 552 000 OPG. Three cases of abomasal cryptosporidiosis slaughtered at the age of 81, 157 and 236 days were examined histologically and ultrastructurally [transmission electron microscopy (TEM) and scanning electron microscopy (SEM)]. Cryptosporidium infection of the abomasum was located in the upper half of the mucosal glands in the plicae spirales of the fundus, corpus and near the ostium omasoabomasicum. Cryptosporidia were not located in the glandular epithelium of the pars pylorica in the abomasum minimally 10 cm from pylorus. Histopathological changes in the site of cryptosporidial infection in the abomasum had a non-inflammatory character and included distinctive dilatation of infected parts of the glands with atrophy and metaplasia of the glandular epithelial cells, goblet cell activation and mucus hyperproduction. The TEM revealed a relatively small number of Cryptosporidium life cycle stages attached to glandular epithelial cells. In SEM the inner mucosal abomasal surface appeared swollen but was never infected by cryptosporidia.
Keywords: Cattle; Animals; skot; novorozená zvířata; Female; feces; Feces; Prevalence; polymerázová řetězová reakce; Pedigree; Microscopy, Electron; Polymerase Chain Reaction; ženské pohlaví; rodokmen; Animals, Newborn; Cryptosporidiosis; elektronová mikroskopie; prevalence; nemoci skotu; Cattle Diseases; DNA, Protozoan; Male; Czech Republic; protozoální DNA; Parasite Egg Count; počet parazitárních vajíček; Česká republika; kryptosporidióza; zvířata; mužské pohlaví; Cryptosporidium